Risk analysis of tooth extraction in hypertensive patients under ECG monitoring: a single-center retrospective study - Yifan Yang; Wenying Wang; Ying Ji; Xiangliang Xu; Chengge Liu; Jingyi Li (BMC Oral Health)
Abstract Objectives This study aimed to identify risk factors associated with intraoperative hypertension and new-onset electrocardiographic (ECG) abnormalities in hypertensive patients undergoing tooth extraction. Materials and methods This case-control study included 2,059 cases of tooth extractions performed in hypertensive patients under intraoperative ECG monitoring at Peking University School and Hospital of Stomatology. Blood pressure (BP) and heart rate (HR) were recorded at four key time points. We specifically analyzed patients who required antihypertensive intervention and those with new-onset intraoperative ECG abnormalities, employing logistic regression to identify independent risk factors. Additionally, ROC curves were used to determine the optimal cutoff points for linear variables, thereby developing the most effective predictive model. Results A total of 8.01% of patients required temporary intraoperative antihypertensive medication for blood pressure control, while 37.20% exhibited transient intraoperative ECG abnormalities. Only two cases resulted in temporary procedure termination due to inadequate blood pressure control, while all other procedures were successfully completed. Preoperative systolic blood pressure(SBP) ≥ 159 mmHg (AUC = 0.91, Sensitivity = 84.24%, Specificity = 88.75%) and operative time (OR = 3.620, P<0.001) were significantly associated with intraoperative blood pressure fluctuations. In addition, sex (OR = 0.796, P = 0.019), age (OR = 1.024, P < 0.001), history of cerebrovascular disease (OR = 1.301, P = 0.020), SBP at the start of the operation (OR = 1.011, P = 0.006), number of teeth extracted per session (OR = 1.182, P < 0.001), and estimated operative time (OR = 1.236, P = 0.017) were all significantly associated with new-onset intraoperative ECG abnormalities. Conclusions Intraoperative hypertension was strongly associated with preoperative SBP ≥ 159 mmHg and prolonged operative time. New-onset intraoperative ECG abnormalities were significantly associated with both patient-related factors (age, sex, cerebrovascular disease, baseline BP) and procedural variables (number of teeth extracted, and operative time). Clinical relevance This study provides evidence-based recommendations for optimizing cardiovascular risk management in hypertensive patients undergoing oral procedures, highlighting the need for individualized monitoring strategies.